Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1051/e3sconf/202131602003
|View full text |Cite
|
Sign up to set email alerts
|

Innovation attributes and their linkages to behavioral drivers of farmers’ intention to adopt True Shallot Seed

Abstract: True Shallot Seed (TSS) has been promoted as an alternative solution to overcome shallot yield problems in Indonesia. A case study method was employed to assess perceptions of innovation attributes and their linkages to behavioral drivers of farmers’ intention to adopt TSS. Respondents were shallot farmers in Cirebon and Brebes involved in participatory on-farm trials. All innovation attributes, i.e. relative advantage, compatibility, complexity, triability and observability are perceived as positive by farmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…It is known that economic benefits are among the incentives for farmer innovativeness (Läpple et al, 2015). Besides striving for higher revenues, attitudes about self-realization and well-being are also crucial incentives for innovativeness (Adiyoga, 2021;Läpple et al, 2015;Walder et al, 2019). Shah et al (2016) reported that attitudes were significant predictors of farmers' innovativeness in hybrid rice.…”
Section: Crop Sciencementioning
confidence: 99%
“…It is known that economic benefits are among the incentives for farmer innovativeness (Läpple et al, 2015). Besides striving for higher revenues, attitudes about self-realization and well-being are also crucial incentives for innovativeness (Adiyoga, 2021;Läpple et al, 2015;Walder et al, 2019). Shah et al (2016) reported that attitudes were significant predictors of farmers' innovativeness in hybrid rice.…”
Section: Crop Sciencementioning
confidence: 99%